Fatigue vibration monitoring using Laser Doppler for dissimilar joint of cracked materials - Nozie, Abdullah; Al Imran, Ismail; Shahruddin, Mahzan@Mohd Zin; Ahmad Mujahid, Ahmad Zaidi; Imran, Ghazali (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.